Practice of using plant and synthetic derivatives of anticancer drugs among cancer patients at NICRH, Bangladesh - Hasnat, Najib (BRAC Univeristy, 2018)
This project report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2017.